Položaj prokurista v pravdnem postopku - Galič, Aleš (Podjetje in delo, 2014)
The Slovenian Companies Act, by making reference to acts within the legal capacity of the company, limits the powers of a specially authorized representative (prokurist) to acts in the sphere of substantive law. On the contrary, such a representative, unless specially authorized by the company's legal representative, cannot perform procedural acts, such as filing a lawsuit or an appeal or giving a power of attorney to a legal counsel to bring proceedings. Procedural acts are not covered by a legal capacity but by a capacity to sue and be sued. The case law of the Supreme Court of the Republic of Slovenia concerning this issue is divergent, which jeopardizes legal certainty and predictability as well as the right to equality before the law. The current regulation is unsatisfactory. The legislature should urgently intervene. Following the regulation in relevant foreign legislation (German, Austrian, Croatian) it should ensure that a prokurist will be empowered already by the law to perform procedural acts as well.
Keywords: gospodarske družbe; pooblastila; pravdni postopek; prokuristi; reševanje; spori; zastopanje